Attitude as the mediating von the relationship between dressing behavior with awareness and perception on dress code among students - Tan, Jian Shiang; Wok, Saodah (2018)
Recently, it is observed that students of the International Islamic University Malaysia (IIUM), Gombak campus are deteriorating in their dressing and some do not wear clothes according to the Dress Code laid down by IIUM. This has caught the attention of the Students Council. As such, the objectives of this research are (1) to analyze the relationship between awareness, perception, attitude and dressing behavior and (2) to determine the mediating effect of attitude on the relationship between awareness, perception and dressing behavior. The Social Rule System Theory is used to explain the effects of awareness, attitude and dressing behavior. This study employs a quantitative research design using the survey method with questionnaire as the research instrument. Using the stratified random sampling, a total of 400 students from the Gombak campus participated in the study. Results show that there is a positive relationship among all variables. Attitude fully mediates the relationship between dressing behavior and awareness while it only partially mediates the relationship between the dressing behavior and perception. Therefore, attitude does play a significant role in affecting the dressing behavior of students in IIUM.